Influência do comportamento do usuário no consumo energético de habitações multifamiliares em Santa Maria, RS - Zambonato, Bruna (2021)
Occupancy, window and shading operation, heating and cooling systems use and setpoint are examples of actions related to occupant behaviour and are associated with thermal comfort and energy performance in homes. A better understanding of occupant behaviour contributes to reducing the gap between estimated and actual building performance and values the human factor as a factor as important as technological innovations in building efficiency. The present work aims to analyse the influence of occupant behaviour related to thermal comfort on energy consumption in multifamily residential buildings with 1 to 3 bedrooms in Santa Maria, RS. Qualitative research was applied to identify the main adaptive behaviours and motivations from the perception of 9 households of multifamily housings with similar building characteristics, to contextualize the next stage with local vocabulary and culture. In the second stage of the research, a survey applied to 155 households investigated the occupant’s perception of thermal comfort, habits, and motivations for certain adaptive behaviours. Monthly energy consumption was also surveyed for 51 of these respondents, to identify the influence of occupant behaviour on energy consumption. The results indicate that users are active and interact with the building in different ways to achieve thermal comfort. The main controls adopted are individual adjustments, such as changing clothes, cold or hot drinks and cold or hot baths. To minimize heat discomfort, occupants also use the air conditioner (AC) more often than the fan and windows. For discomfort from cold, heating equipment such as AC and electrical heater are only used if individual adjustments and closing the windows are not enough to achieve thermal comfort. Family income influenced the frequency of AC (heating) use, and age group influenced the type of adaptive behaviour adopted by young and old households. The AC usage pattern and setpoint were the main factors influencing the energy consumption. It was possible to identify typical occupant behaviour profiles, with varied occupancy, window, and AC use, which resulted in different energy consumption. Results indicate the diversity of occupant behaviour in multifamily residential buildings. Therefore, the importance of enabling different adaptive behaviours is highlighted, especially passive conditioning strategies, to reduce the energy consumption of buildings.